Mapping the Skills of Migrants for Developing Social Innovation, Art, and Design Workshops - Reaes Pinto, Paula (2020)
This transdisciplinary research is framed by the fields of heritage and socially engaged Art and Design. This work stems from a set of projects developed and supported by the Aga Khan Foundation Portugal, alongside two Portuguese public universities, namely the University of Évora and the Faculty of Architecture of the University of Lisbon. These two projects, Mais Sul and Catapulta, have as their main objective the migrant populations support in the metropolitan area of Lisbon, specifically in Oeiras and Sintra Municipalities, through the identification and mapping of techniques, arts, and crafts developed by migrants from their cultural heritage, which are rarely known and valued. Another objective is to enhance arts and crafts as a way to improve livelihoods, and through that we foster the creation of design workshops, contributing to the sociocultural participation of people but also to build social cohesion and local economic growth. The article introduces the grassroots methodology for mapping, the relational and dialogical process, including the data collection process and tools resulting from the case studies.